Mainstreaming the Position of Media for Good Governance in Combating Corruption in Indonesia - Alam, Muhammad Bachrul; Haidar, Hafid Umar; Shafei, Muhammad; Abidin, Muhammad Irfanul; Malik, Akbar Sauqi (Indonesia Media Law Review, 2022)
Media is one of the important pillars in democracy. In many conditions, the media is also considered to have an important role in encouraging the creation of good governance, one of which is encouraging massive efforts to prevent corruption and enforce the law. Various cases prove that with various media discourses and types of news in the community, it helps encourage various disclosures of corruption cases and encourages cleaner, transparent, and better governance. This study aims to analyze the prevention of corruption through good governance through media encouragement. This study also aims to describe and analyze the role of the media in encouraging various efforts to prevent corruption. The method in this study is a normative legal study where the research only examines various theories and legal norms as well as social theories in corruption and governance.